2013
DOI: 10.3748/wjg.v19.i4.536
|View full text |Cite
|
Sign up to set email alerts
|

Cdx2 expression and its promoter methylation during metaplasia-dysplasia-carcinoma sequence in Barrett's esophagus

Abstract: Cdx2 expression is restored irrespective of the methylation status of its promoter. Apparent positive immunohistochemical results can be a molecular mark for gene silencing memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…2D), functional transcriptional activity of BOB.1 may have been lost or reduced by mechanisms other than epigenetic gene silencing. Indeed, similar phenomena, that genes once silenced by DNA hypermethylation of cancer cells can be significantly but transiently reactivated through chromatin remodeling without any changes in DNA methylation, have been described in several cell lines [16] and in the metaplasia-dysplasia-carcinoma sequence in the Barrett esophagus [13]. Therefore, when interpreting immunohistochemical results for diagnostic or research purposes, we must bear in mind that apparent positive immunostaining could merely be the result of chromatin remodeling [16] and that such transient expression often has little functional significance.…”
Section: Discussionmentioning
confidence: 93%
“…2D), functional transcriptional activity of BOB.1 may have been lost or reduced by mechanisms other than epigenetic gene silencing. Indeed, similar phenomena, that genes once silenced by DNA hypermethylation of cancer cells can be significantly but transiently reactivated through chromatin remodeling without any changes in DNA methylation, have been described in several cell lines [16] and in the metaplasia-dysplasia-carcinoma sequence in the Barrett esophagus [13]. Therefore, when interpreting immunohistochemical results for diagnostic or research purposes, we must bear in mind that apparent positive immunostaining could merely be the result of chromatin remodeling [16] and that such transient expression often has little functional significance.…”
Section: Discussionmentioning
confidence: 93%
“…It is believed that there is a close relationship between inflammatory responses and transcription factors since replacement of damaged tissues normally starts by cell proliferation. Subsequently, chronic inflammation can persuade unrestrained proliferation, which leads to the production of unwanted proteins as a result of CDX genes or even p53 gene (Makita et al, 2013). Since apoptosis is usually programmed by p53 to disregard death or abnormal cells in the cell cycle by binding to TNF receptors and Fas, any disruption in this pattern will results in unwanted cells.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL 1 and CXCL 3 play a role in spinal cord development by inhibiting the migration of oligodendrocyte precursors . CDX 1 and CDX 2 genes are essential for skeletal and intestinal development . These genes are usually expressed in the mucosal epithelium from the duodenum to the rectum, but one study demonstrated their presence in EAC tissue …”
Section: Normal Squamous Mucosa → Inflammation (Gerd) → Be Metaplasiamentioning
confidence: 99%